FACTORS OF SOIL SENSITIVITY TO EROSION IN VOLYN REGION - Matviichuk, B. V.; Matviichuk, N. H. (Scientific Progress & Innovations, 2020)
Swamp and peat-swamp soils on different rocks and alluvial deposits, lowland peat and peat-swamp soils and sod carbonate soils mainly on the eluvium of dense carbonate rocks are characterized by the greatest heterogeneity in terms of sensitivity to wind erosion. The most homogeneous in this respect are mediumdeep loam black soils, medium-loam podzolic black soil and deep medium-loam black soils. Swamp and peat-swamp soils on different rocks, lowland peat and peat-swamp soils and sod carbonate soils mainly on the eluvium of dense carbonate rocks are the least sensitive to wind erosion. The soils of the northern part of the region, which have a very high content of organic matter, are the least sensitive to wind erosion. Also, a moderate level of sensitivity to wind erosion is characteristic of the southern part of the region, where soils have a heavier mechanical composition. The smallest share of the fraction sensitive to wind erosion was found in the soils of Horokhiv (0.42), Liubeshiv (0.42) and Ivanychiv (0.43) districts. The most homogeneous conditions in terms of soil sensitivity to erosion as to variation coefficient of the soil fraction content that may undergo wind erosion are in Lutsk (CV=5.12 %), Horokhiv (CV=6.24 %) and Kivertsiv (6.8 %) districts. The most heterogeneous conditions according to this criterion are in Liubeshiv (CV=18.18 %), Ratniv (CV=13.47 %) and Shatsk (11.45%) districts. The highest level of wind erosion is forecasted for the administrative districts of the region, which are located in the west and north-west. The projected area with virtually no or little deflation is most characteristic of the south-eastern parts of the region. The ratio between areas with small and moderate levels of air erosion determines the average level of soil erosion losses in the administrative district.